2013
DOI: 10.1186/1472-6963-13-131
|View full text |Cite
|
Sign up to set email alerts
|

Resource utilization, costs and treatment patterns of switching and discontinuing treatment of MS patients with high relapse activity

Abstract: BackgroundMultiple sclerosis (MS) is a chronic disease that affects mainly adults in the prime of their lives. However, few studies report the impact of high annual relapse rates on outcomes. The purpose of this study was to identify high relapse activity (HRA) in patients with MS, comparing differences in outcomes between patients with and without HRA.MethodsA retrospective longitudinal study was conducted using the MarketScan® Commercial Claims and Encounters and Medicare Supplemental Database. Patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
(20 reference statements)
2
24
1
Order By: Relevance
“…Accordingly, previous studies showed that financial consequences of relapses depended not only on the temporary loss of productivity, but also on the subsequent change of treatment [3537]. Indeed, overall annual healthcare costs, although not being associated with the risk of the first relapse, were positively correlated to the ARR.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, previous studies showed that financial consequences of relapses depended not only on the temporary loss of productivity, but also on the subsequent change of treatment [3537]. Indeed, overall annual healthcare costs, although not being associated with the risk of the first relapse, were positively correlated to the ARR.…”
Section: Discussionmentioning
confidence: 99%
“…But decisions to change inevitably involve cost in themselves-these are called switching costs (or sometimes switching barriers). Switching costs are not unique to medical education -they occur in all walks of life[5]. If switching costs are too high, they can cancel out any savings made as a result of going with a lower cost purchase.…”
Section: Dear Editormentioning
confidence: 99%
“…Of those that switched or discontinued, significantly higher health care utilization occurred during the 18-month follow-up period compared with those who were persistent on their original index drugs. Raimundo et al (2013) conducted a subgroup analysis on switchers and discontinuers and found that high relapse activity predicts switching or discontinuing from DMTs among MS patients who had used a DMT previously. 38 Our study adds to this research by correlating changes in persistence status with relapse outcomes for natalizumab specifically.…”
Section: Mean Relapse Outcomes In Year Prior To Treatment Transitionmentioning
confidence: 99%
“…23,38 used PharMetrics PatientCentric Database to analyze health care resource utilization during an 18-month period after discontinuation or switch from an IFN or GA. 23 The authors found that about half of patients remained on their index drugs. Of those that switched or discontinued, significantly higher health care utilization occurred during the 18-month follow-up period compared with those who were persistent on their original index drugs.…”
Section: Mean Relapse Outcomes In Year Prior To Treatment Transitionmentioning
confidence: 99%